Efetividade clínica comparativa do análogo de Insulina Glargina com Insulina NPH para tratamento de pacientes com Diabetes Mellitus tipo 1 - Gerusa Carla Correa de Oliveira (2015)
The insulin analogue glargine is dispensed, in the state of Minas Gerais, to patients with diabetes mellitus type 1 that attend to criteria of Health Secretariat of Minas Gerais (SESMG). Currently about 3200 patients are benefit, corresponds to R$11 million annual. However, results of several studies with high scientific rigor have not been demonstrated the superiority of insulin analogue glargine in glycemic control of patients, compared to standard treatment. In order to evaluate the clinical effectiveness of insulin analogue glargine compared to recombinant DNA NPH insulin, we performed a non-concurrent cohort study of patients with type 1 diabetes, who received insulin analogue glargina through specialized component / high cost of the SES-MG. Data were collected from administrative procedures of 157 patients that have requested inclusion in the program between January 2011 and December 2013. Patients were compared to themselves in a real world scenario, before and after six, 12 and 18 months using the analog of insulin glargine. The glucose level of patients was assessed by laboratory results of glycosylated hemoglobin A. The paired t-test was used to compare the data. It was calculated the frequency of patients with adequate glycemic control forward reference values has been established in the literature. From the glycemic control, patients were classified into benefit or not benefit with treatment. It was evaluated thefrequency of patients who complied with the clinical protocol, which determines the 50% reduction on the value exceeding in glycosylated hemoglobin A, compared to the previous evaluation. It was evaluated also the decrease of hypoglycemic crisis. The analysis of Hb1Ac values demonstrated better clinical effectiveness in treatment with insulin analogue glargine compared to treatment using NPH insulin, at 18 months of follow up It was verified the decrease of hypoglycemic crisis to 51% of patients. The frequency of patients with glycemic control varied from 20.4% to 24.2% at 18 months. Among the 157 participants, only 39(24.8%) were considered benefited with treatment. It was observed compliance with the clinical protocol to 24,2% of patients. The cost of analogous is R$ 258,77 (10 mL vial), while the cost of NPH insulin R$11,57 (10 mL vial), that represents a difference of 2136% in thecost of medicine for the SUS. Due to the low clinical effectiveness and the high cost of the drug, it is concluded that the policy on the about availability of glargine insulin analogue in the state of Minas Gerais, and in other Brazilian states where the analogue is provided, shouldbe reassessed. The divestment and / or renegotiation of prices should be grounded in the results of clinical effectiveness associated with other criteria such as cost-effectiveness 9 evaluation, safety and quality of life of the patient, thus allowing, the reallocation of resources